The prevalence of erythrocyte alloimmunization in clinical practice: A hospital-based study - Inas Bashar Faisal; Mohammed Saleem Abbas; Zahraa Akram Thabit; Dhargam Muhamed Aljebouri; Yakoob Abdulwahid Almusawi (Iraqi Journal of Hematology)
BACKGROUND: One of the complications of blood transfusion is the development of red cell alloimmunization. Little published literature on the prevalence and actual significance of red cell alloantibodies among nonregularly transfused patients and the general population. OBJECTIVES: This study aimed to estimate red cell alloantibodies’ prevalence, specificity, and clinical significance in obstetric and medical practice in Iraq. MATERIALS AND METHODS: A cross-sectional hospital-based study involving internal medicine patients and ladies in obstetric wards of Baghdad Teaching Hospital in Baghdad/Iraq, from January 2022 to May 2022. Demographic data were collected along with detailed medical, obstetric, and transfusion history. Alloantibody screening was performed, and samples with positive results were subjected to antibody titration and identification. RESULTS: A total of 200 patients were enrolled. Indirect antiglobulin test was positive in 15% of patients in internal medicine wards and 23% of ladies in obstetric wards, with most of the identified alloantibodies being clinically significant, against Kidd and Duffy antigen groups. Blood transfusion of more than four units to patients at internal medical wards showed a significant association as a risk for developing red cell alloantibodies (P = 0.025). For ladies in obstetric wards, there was a significant association between pregnancy loss at the time of screening and alloimmunization (P = 0.0164). CONCLUSION: High prevalence of red cell alloantibodies in comparison to what is published worldwide. Transfusion of more than four units of blood and pregnancy loss at the time of screening were statistically significant risks for alloimmunization of the medical and obstetric populations, respectively.